2013
DOI: 10.1542/peds.2013-1580
|View full text |Cite
|
Sign up to set email alerts
|

Association of Constipation and Fecal Incontinence With Attention-Deficit/Hyperactivity Disorder

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Several studies have shown that behavioral problems can be associated with defecation and voiding disorders, although few studies have looked directly at a link between a diagnosis of attention-deficit/hyperactivity disorder (ADHD) and constipation or fecal incontinence. WHAT THIS STUDY ADDS:We identified an increased risk for both constipation and fecal incontinence in children with ADHD. In patients with concomitant ADHD and defecation disorders, more aggressive medical and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 20 publications
6
68
2
2
Order By: Relevance
“…These results confirm those of previous clinical studies of ADHD comorbidity that have reported increased frequencies of allergies and asthma, 55,56 headaches and migraine, 57,58 enuresis, 40,41,43,59,60 and gastrointestinal or bowel problems. 47 The authors also confirm findings of prior community studies that document poorer health in general among those with ADHD, 2,18,22,34,61,62 as well as associations with specific medical conditions including allergies and asthma, 22,[34][35][36]39,[63][64][65] headaches/migraine, 22,34,66 enuresis, 42,44,45,67 and gastrointestinal/bowel problems. 22,46,67 The confirmation of comorbidity in the general population demonstrates that the associations are not an artifact of clinical samples that are characterized by more severe, comorbid conditions.…”
Section: Discussionsupporting
confidence: 84%
“…These results confirm those of previous clinical studies of ADHD comorbidity that have reported increased frequencies of allergies and asthma, 55,56 headaches and migraine, 57,58 enuresis, 40,41,43,59,60 and gastrointestinal or bowel problems. 47 The authors also confirm findings of prior community studies that document poorer health in general among those with ADHD, 2,18,22,34,61,62 as well as associations with specific medical conditions including allergies and asthma, 22,[34][35][36]39,[63][64][65] headaches/migraine, 22,34,66 enuresis, 42,44,45,67 and gastrointestinal/bowel problems. 22,46,67 The confirmation of comorbidity in the general population demonstrates that the associations are not an artifact of clinical samples that are characterized by more severe, comorbid conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Firstly, a relationship between the learning problems and either the sustained attention problems or the psychiatric disorders could not be supported by our data. Secondly, we hypothesised that the problems could be associated with the bowel management, as a relationship between attention deficit disorder and constipation has been described in the literature . However, this hypothesis could not be confirmed with regression analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, chloride ions and bicarbonate ion are secreted into the intestinal lumen with concomitant secretion of fluid . The GC‐C receptor has a genetic polymorphism associated with attention deficit/hyperactive disorder which is highly comorbid with pediatric constipation . To our knowledge, the distribution pattern and functional role of this common polymorphism of GC‐C receptor gene has not been reported in healthy controls and patients with IBS‐C in the USA, Europe, or Japan .…”
Section: Discussionmentioning
confidence: 99%